(untitled) (Gilgameš, 2019)
The analysis of several unpublished letters by or to Paolo Paruta (1540-1598) could be very useful to revalue this underrated Venetian political writer, author of the dialogue Perfettione della Vita Politica (’About Perfection of Political Life’) and Ambassador for the Republic of Venice at the Papal Court (1592-1595). In fact, these letters shed some light on the daily life of Paruta’s political praxis: his travels, his duties as ambassador, his relationships with foreign sovereigns and with Venetian fellow citizens, his growing reputation; thanks to them, we could understand why Ugo Foscolo wanted Paruta to be studied in university courses as politico pratico. Some other letters (such as the one about the dedication of Discorsi Politici’s first edition, 1599), written by Paruta’s brother and sons, proof the hard economical situation of the ambassador’s heirs after Paolo’s death. In the last part of the essay there’s an analysis of a passage of a letter by Polish political writer Krzysztof Warszewicki about the project of a Latin translation of Paruta’s political work: then comes a comparison between Warszewicki’s and Paruta’s political thought.